PENERAPAN MEDIA PEMBELAJARAN SAINS PADA ANAK USIA DINI ”MERDEKA BELAJAR” DI ERA BELAJAR DI RUMAH - Adnyani Ni Wayan (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Medium learning science for early childhood is a tool for exploration and developing scientific values and the ability to think logically. Research is designed with a qualitative approach. The issues to be discussed between laun (1) How was the process of implementing independent science learning “Merdeka Belajar” in the early age children at home TK Werdhi Kumara Punggul. (2) Is the tone of children aged in the learning era humbled at kindergarten Werdi Kumara Punggul. This research aims to describe the learning process, describes the efforts in the process teaching of sains at TK Werdi Kumara Punggul. The theory used for analyzing the problem is the constructivist theory of Piaget, this research was carried out from November 2020 to February 2021 with research location at TK Werdi Kumara Punggul, Abiansemal, District Badung regency. The research subjects were teachers, children aged 4-5 years which amounted to 5 children. The method used in this study is the qualitative descriptive method. data collection techniques through observation direct interviews, documentation, and literature study data analysis techniques used analysis and arranged in a description data reduction, presentation and drawing conclusions the results of the study sho the process of applying the media learning science “Merdeka Belajar” in early childhood learning at home divided into 3 stages, namely the planning, implementation, and evaluation stages, with the learning method used namely telling stories, questions and answers.